(untitled) (Серія: Історія. Політологія, 2021)
У статті аналізується публікаційна діяльність вчених Одеського товариства історії й старожитностей й характеризується їхній внесок у військово-історичні дослідження Наддніпрянської України й Кримського півострова. У процесі наукової розвідки з’ясовано, що поряд із загально-археологічними, товариством презентувалися дослідження, пов’язані з військовою археологією й військовою історією. Означена проблематика, піднімалася у публікаціях вчених: Ф. Бруна, К. Стаматі, І. Кареліна, О. Кочубинського. Військово-історичні дослідження були представлені у кількох площинах: топографія, вивчення й охорона фортифікаційних споруд, військове протистояння Російської й Османської імперій, історія українського козацтва. Особлива увага товариством була приділена фортецям у Аккермані, Хотині, Ізмаїлі. The purpose of the study is to analyze the publishing activities of scientists of the Odessa association of History and Antiquities and to determine their contribution to the military-historical research of the Dnieper Ukraine Ukraine and the Crimean Peninsula. The methodology of the study is based on the principles of historicism, systematic, scientific, interdisciplinary. The following general historical methods have been used: historiographic analysis, historical-genetic, terminological analysis, comparative, typological. The author adheres to the civilization approach. Scientific novelty: the contribution of the Odessa association of History and Antiquities to the military-historical studies of the Dnieper Ukraine and the Crimean Peninsula is characterized on the basis of a wide range of published researches. Conclusions. Along with general archeological, the association presented studies related to military archeology and military history. The problems identified were raised in the publications of scientists: F. Brun, K. Stamati, I. Karelin, O. Kochubinsky. Military-historical studies were presented in several areas: topography, study and protection of fortifications, military confrontation of the Russian and Ottoman empires, history of Ukrainian Cossacks. The problems concerned the South of Ukraine, Crimea, Bessarabia. Particular attention was paid to the fortresses in Akkerman, Khotyn, Ishmael. The main topics of the publications were the Russo-Turkish wars, as well as individual episodes and processes related to them. A profound, professional analysis of events, in publications, combined with political engagement and duplication of existing imperial ideologues. Archaeographic surveys mainly concerned personal sources that reflected the local governance of Russian military officials in the Black Sea Fleet and fortifications, and described Turkish and Tatar campaigns. Although the research was largely sporadic, it resulted in the publication of a considerable amount of material and concentration in the Museum of the Society of Antiquities and Cartographic Sources.